A rare case of siliconomas resulting from free silicone injections in breast tissue - Gifuni, Rossella; Eusebi, Laura; Masino, Federica; Testini, Valentina; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2023)
One of the most common complications of free silicone injection at multiple sites is its leakage and more rarely its migration through the lymphatic system with a resulting local inflammatory reaction of granulomatous type, known as “siliconoma”. This report describes the case of a young woman who came to our attention for bilateral mastodynia and palpable tumefactions in breast and gluteal region, a few years after percutaneous injections of free liquid silicone for breast augmentation.